2020
DOI: 10.1080/08985626.2020.1757159
|View full text |Cite
|
Sign up to set email alerts
|

Meeting entrepreneurs’ expectations: the importance of social skills in strong relationships

Abstract: In this study, we are interested in whether and when individuals' ability to interact with others influences their tendency to provide social support to nascent entrepreneurs. We argue that social skills are not only necessary for entrepreneurs to obtain resources, but also important for those people (alters) providing entrepreneurs with support, and especially so in strong relationships.We argue that in strong relationships, expectations of social support exchange pressure potential support providers to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 94 publications
1
9
0
1
Order By: Relevance
“…Due to the changing conditions of the 21st century, it is thought that working as a team during STEM activities will be beneficial in solving the problems they face in daily life (Çorlu, 2014). In order for students to have entrepreneurship characteristics, they must be raised as an individual with social skills and open to group work (Baron and Markman, 2000;Nielsen and Klyver, 2020). In this study, the data obtained from the SBES showed that while students' scores '"risk taking", "need for success" and "communication" sub-dimensions increased after the Entrepreneurship-oriented STEM activities, there was no statistically significant difference in team skills.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Due to the changing conditions of the 21st century, it is thought that working as a team during STEM activities will be beneficial in solving the problems they face in daily life (Çorlu, 2014). In order for students to have entrepreneurship characteristics, they must be raised as an individual with social skills and open to group work (Baron and Markman, 2000;Nielsen and Klyver, 2020). In this study, the data obtained from the SBES showed that while students' scores '"risk taking", "need for success" and "communication" sub-dimensions increased after the Entrepreneurship-oriented STEM activities, there was no statistically significant difference in team skills.…”
Section: Discussionmentioning
confidence: 77%
“…Öğrencilerin 21.yüzyılın değişen şartlarından dolayı STEM etkinlikleri sırasında takım olarak çalışmasının günlük hayatta karşılaştıkları problemleri çözme konusunda yarar sağlayacağı düşünülmektedir (Çorlu, 2014). Öğrencilerin girişimci özelliklerine sahip olması için sosyal becerilere sahip ve grup çalışmasına açık bir birey olarak yetiştirilmesi gerekir (Baron ve Markman, 2000;Nielsen ve Klyver, 2020). Bu çalışmada, girişimcilik becerilerinin ölçüldüğü FTGÖ'nden elde edilen veriler öğrencilerin Girişimcilik odaklı STEM etkinlikleri sonrasında "risk alma", "başarı ihtiyacı" ve "iletişim" alt boyutlarında istatiksel olarak anlamlı artış olduğunu ortaya koyarken "takım çalışması becerileri" alt boyutunda istatistiksel olarak anlamlı bir fark görülmemiştir.…”
Section: Tartışma Ve Sonuçunclassified
“…Both approaches neglect the ‘everyday’ occurrences of social support (Suurmeijer et al, 1995), viewing it either as something that exists or not, or as simply a solution to a time-bound problem. Furthermore, this deterministic perception of social support largely overlooks the interactive dynamics and agency involved in this process (Chen and Klyver, 2021; Nielsen and Klyver, 2020). After all, social support is not merely ‘a commodity that resides in the provider and passes to the recipient’ (Gottlieb and Bergen, 2010: 512), but requires interpersonal activities performed by both.…”
Section: Research On Households and Social Supportmentioning
confidence: 99%
“…As the process of starting and growing a business is resource intensive and emotionally demanding (Braun and Sieger, 2021;Cardon et al, 2012), entrepreneurs can greatly benefit from the social support (i.e. instrumental and emotional support) that network members provide (Kim et al, 2013;Nielsen and Klyver, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation